Problems in anticoagulation of a patient with antibiotic treatment for endocarditis: interaction of rifampicin and vitamin K antagonists. (12th February 2018) - Mizera, Lars; Geisler, Tobias; Mörike, Klaus; Gawaz, Meinrad; Steeg, Martin
Abstract : The cytochrome P450 is a superfamily of isoenzymes that are responsible for the metabolism of many drugs. Significant changes in pharmacokinetics and drug interactions may be due to induction of hepatic cytochrome P450 enzymes. Rifampicin is a common inducer of CYP3A4. We report a case of a 57-year-old woman who was suspected for endocarditis and therefore treated with rifampicin. Due to previous mechanical aortic valve replacement, she also received phenprocoumon for anticoagulation. Although continuing anticoagulant therapy, antibiotic coadministration led to normal international normalised ratio (INR) level. Fifteen days after the treatment with rifampicin ended, INR returned to therapeutic level.